Analisis Penggunaan Teknologi Informasi dalam Pembelajaran Sejarah di Era Digital pada Madrasah Aliyah Darul Hikmah Tawangsari - Destina Suci Fitriani; Dita Hendriani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to analyze the use of Information and Communication Technology (ICT) in history learning at Madrasah Aliyah Darul Hikmah Tawangsari. The background of this study is based on the rapid development of ICT in the era ofe the industrial revolution 4.0 which has an impact on the education sector, especially in Islamic boarding school-based institutions. Thisc study usesa a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the Darul Hikmah Islamice Boarding Schoole has succeeded in integrating ICT into history learning through the preparation of a Learning Implementation Plan (RPP), preparation ofe learning media, and implementation of ICT-based learning. The application of ICT has been proven to increase students' interest, activeness, and understanding of history material. This study provides an overview of the strategy of ICT integration in history learning in the Islamic boarding school environment and its positive implications for the quality of learning.